PENGARUH PROJECT BASED LEARNING TERHADAP MOTIVASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PKn DI SMP - Yoakim Yordianus Gusi (Jurnal Rontal Keilmuan Pancasila dan Kewarganegaraan, 2019)
This study aims to determine the effect of project based learning on the learning motivation of students in SMP. The research approach used is a quantitative approach type of quasi experimental research with a two-group post-test-only design. This type of research can help ins finding the relationship between independent variables and dependent variables from various situations. Based on the results of the post-test analysis of the experimental class and the control class, the presentation of the increase in student motivation in PKn subjects had a very significant difference between the two classes. In the experimental class with the number of respondents 29 people got a presentation of 89.6% from the results of the presentation stated very well based on the interval table criteria for increasing student learning motivation with very good presentations intervals of 84% -100%. While the presentations obtained in the control class with the number of respondents 20 people received a percentage of 55.2%. From the results of the presentation, it states that it is quite good based on the criteria table for increasing student learning motivation with fairly good percentages 52% -68%.